Frères et sœurs: une relation de parenté au cœur des enjeux de la nomination de l’enfant à la naissance - Tillard, Bernadette (Rivista Italiana di Educazione Familiare, 2011)
The birth of a child is not only a biological event, but also a social one. From childbirth, parents welcome the baby and include him/her in the nuclear and extended family by choosing name(s) and surname. These names but also food and mothering care will be marked by two joint but opposed movements: accentuate the uniqueness of the newborn or emphasize its resemblance to his/her siblings. This article examines the signs of this double movement through the results of an ethnographic study conducted in a district of the city of Lille where the population generally has fewer economic resources than the average population in France.